Expression of Culture Diversity Through Creation of Zapin Nusantara Berlenggang Dance - Robby, Robby Hidajat; Iziq, Iziq Eafifi Ismail; Afaf, Muhammad 'Afaf Hasyimy; Surasak, Surasak Jamnongsarn (Mudra Jurnal Seni Budaya, 2024)
This article elaborates on Nusantara diversity as a phenomenon that underlies the creation of the Zapin Nusantara Berlenggang dance. In many regions, the characteristic of Zapin dance has grown through evolution that involves the unity of various ethnicities, mainly ethnics living in the coastal area. Such unity is a strong pillar that supports the Republic of Indonesia. Although the political situation is fluctuating, there is still an effort to empower local potentials to maintain diversity in Indonesia. The exploration of the Nusantara theme in the creation of the Zapin dance is powerfully relevant to the objective of this research, which is to strengthen the unity of Indonesia through its pluralistic nature. The creation of Zapin dance with the Nusantara theme will be understood through the approach of creation process experience, which, thus, is the type of this research that is explorative qualitative descriptive. In other words, this research is developmental research that emphasizes exploring the creation process. The research data are collected through three procedures respectively: interviews with Zapin dance patrons in Palembang, Pekanbaru Riau, Gresik, and Malang; dance technique exploration conducted in Malang and Gresik; and a dance trial held at the Indonesia Art Institute of Denpasar. The focus of this research is on managing the technical and aesthetical experiences of the dancers to internalize the Nusantara theme into their minds. The research question, therefore, comprises (1) What is the function of Zapin Nusantara Berlenggang dance? Moreover, (2) How is the creation process of Zapin Nusantara Berlenggang dance?